2008
DOI: 10.1038/nature06507
|View full text |Cite
|
Sign up to set email alerts
|

Giant magneto-elastic coupling in multiferroic hexagonal manganites

Abstract: The motion of atoms in a solid always responds to cooling or heating in a way that is consistent with the symmetry of the given space group of the solid to which they belong. When the atoms move, the electronic structure of the solid changes, leading to different physical properties. Therefore, the determination of where atoms are and what atoms do is a cornerstone of modern solid-state physics. However, experimental observations of atomic displacements measured as a function of temperature are very rare, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
320
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 388 publications
(372 citation statements)
references
References 25 publications
36
320
1
4
Order By: Relevance
“…Since the XRD measurements have been performed at room temperature, the obtained structure is the noncentrosymmetric, which allows the appearance of ferroelectricity. Magnetic measurements show a paramagnetic-antiferromagnetic transition at T N ∼75 K, also in good agreement with the values reported in literature [13,14]. Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Since the XRD measurements have been performed at room temperature, the obtained structure is the noncentrosymmetric, which allows the appearance of ferroelectricity. Magnetic measurements show a paramagnetic-antiferromagnetic transition at T N ∼75 K, also in good agreement with the values reported in literature [13,14]. Fig.…”
Section: Resultssupporting
confidence: 80%
“…The refinement of X-ray data show that YMnO 3 samples are single phase and crystallize in the hexagonal structure (space group P 6 3 cm) with corresponding cell parameters a=b=6.1354(1)Å and c=11.3916(3)Å in excellent agreement with the values reported in the literature [13,14]. Since the XRD measurements have been performed at room temperature, the obtained structure is the noncentrosymmetric, which allows the appearance of ferroelectricity.…”
Section: Resultssupporting
confidence: 76%
“…This becomes even more complex in a system such as YMnO 3 where magnetic structures have the propagation vector k = 0, meaning that magnetic reflections occur at the same position as nuclear reflections, causing great difficulty in the refinement of both magnetic and crystal structures [37]. Lee et al [7] observed 'giant' atomic displacements in YMnO 3 from neutron and x-ray diffraction experiments and suggested that these displacements could be responsible for coupling of the magnetic and electric order parameters. However, as remarked by Chatterji et al [37], no explanation was offered as to how correlations between structural and magnetic parameters were avoided and therefore it is difficult to accept this result.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetoelastic coupling effect in YMnO 3 has been the subject of much work in recent years and a series of neutron diffraction experiments has been carried out to monitor changes in lattice parameters and atomic positions at T N [7,10,29,[35][36][37]. Monitoring of changes in atomic positions and bond lengths is difficult due to the small changes involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation